THE OPTICAL PROPERTIES OF CONICAL STRUCTURE DIELECTRIC-METAL-DIELECTRIC - Abrahamyan, T. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
The features of propagation of light wave on a metal-coated conical tip of optical fiber is considered. During the experiment we detected an output radiation from the tip, when the tip came out from the liquid. The peak of output optical intensity is obtained. This process very essentially depends on the position of the fibre top, with the help of which it is possible to find out very weak vibrations of the surface of the liquid.